The Effect of Activity Ratio on Profitability in Automotive Companies and Components Registered on the IDX - Heru Prayitno, Yogo; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
This article consists of a literature review to identify the elements of innovation leadership skills for middle-vocational leaders in the Technical and Vocational Education and Training (TVET) system in Malaysia. The elements of innovation leadership skills are based on transformational theory, innovation leadership theory, the Four Pillars of Innovation theory, innovation models in leadership and organization, competency profiles for innovation leaders, and innovation leadership modality models. Innovation leadership is a synthesis of different leadership styles in an organization to influence employees to come up with creative ideas, products, services, and solutions. In this systematic literature review, among the identified aspects of innovation leadership skills are relationship building, generating ideas, taking risks, decision-making, problem solving, implementation, technology, entrepreneurship, capacity building, and innovation. Without innovation leadership, there will be high possibilities for an organization to work harder in order to succeed. Therefore, the development of innovative leadership skills is essential to be encouraged at all levels of educational leadership, especially for middle-vocational leaders in TVET organizations.